Green Synthesis of Zinc Oxide Nanoparticles using Hibiscus rosa-sinensis Leaves Extract: Structural, Morphological, Bioactivity and Photocatalytic Properties - Rabi, S. Aron; Kennedy, A. Joseph Sagaya (Asian Journal of Chemistry, 2025)
Zinc oxide nanoparticles (ZnO NPs) were synthesized using an eco-friendly green synthesis approach, with Hibiscus rosa-sinensis leaf extract serving as both a stabilizing and capping agent. The bioactive compounds present in the leaf extract facilitated the formation of ZnO nanoparticles by stabilizing the zinc salt precursor during the synthesis process. The resulting ZnO nanoparticles were coated with biomolecules from the H. rosa-sinensis extract, enhanced the biological activity. Comprehensive characterization of the synthesized ZnO nanoparticles was performed using a range of advanced techniques, including X-ray diffraction (XRD) to determine crystalline structure, Fourier transform infrared spectroscopy (FT-IR) to identify functional groups, UV-Vis spectroscopy to analyze the optical properties and electron microscopy (SEM and TEM) to examine their surface morphology and particle size. An 81.3% breakdown of acid black 1 (AB 1) dye was observed in sunlight, with the degradation rate escalating as the irradiation duration increased. The antimicrobial activity against Staphylococcus aureus and Bacillus subtilis show higher results compared to Escherichia coli and Salmonella typhimurium.